Enhanced effects and mechanisms of Syngonium podophyllum-Peperomia tetraphylla co-planting on phytoremediation of low concentration uranium-bearing wastewater. (September 2021) - Yue, Zhang; Dexin, Ding; Guangyue, Li; Haitao, Yi; Kaige, Zhai; Nan, Hu; Hui, Zhang; Zhongran, Dai; Jianhong, Ma; Feng, Li; Jing, Sun; Yongdong, Wang
Abstract: To improve the remediation efficiency of plants on low concentration uranium-bearing wastewater and clarify its strengthening mechanism, Syngonium podophyllum-Peperomia tetraphylla co-planting system was established, the enhanced effects of plants interaction on uranium removal were investigated, the chemical forms, valence states, and subcellular distribution of uranium in plants were confirmed, and the mechanisms of alleviating uranium stress by plants interaction were revealed. In Syngonium podophyllum-Peperomia tetraphylla co-planting system, the total amount of ethanol-extracted uranium and deionized water-extracted uranium with higher toxicity in their roots were reduced by 10.30% and 7.17%, respectively, which reduced the toxicity of uranium to plants. Plants interaction can inhibit the reduction of U(VI) in the root of Peperomia tetraphylla, which is conducive to the transport of uranium from roots to shoots. In addition, uranium in plants mainly existed in the cell wall (54.44%–66.52%) and the soluble fraction (23.85%–32.89%). These results indicated that Syngonium podophyllum and Peperomia tetraphylla co-planting can enhance their effects of uranium removal by alleviating uranium stress with the cell wall immobilization and vacuole compartmentation, improving biomass of plants, increasing bioaccumulation factor and translocation factor of uranium. Highlights: Plants co-planting changed the chemical form of U and attenuated its toxicity. Co-planting increased plant's bioaccumulation factor and translocation factor for U. Co-planting inhibited the reduction of U(VI) in the root of Peperomia tetraphylla. Co-planting increased plant's ability to alleviate uranium stress.